2008
DOI: 10.1016/j.neuron.2008.09.025
|View full text |Cite
|
Sign up to set email alerts
|

A Mammalian Homolog of Drosophila Tumorous Imaginal Discs, Tid1, Mediates Agrin Signaling at the Neuromuscular Junction

Abstract: Summary Motoneuron-derived agrin clusters nicotinic acetylcholine receptors (AChRs) in mammalian muscle cells. We used two-hybrid screens to identify a protein, tumorous imaginal discs (Tid1), that binds to the cytoplasmic domain of muscle-specific kinase (MuSK), a major component of the agrin receptor. Like MuSK, Tid1 colocalizes with AChRs at developing, adult and denervated motor endplates. Knockdown of Tid1 by short hairpin RNA (shRNA) in skeletal muscle fibers dispersed synaptic AChR clusters and impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 52 publications
2
61
0
Order By: Relevance
“…When ATP synthesis is inhibited, TID1 is recruited to a detergent-resistant fraction together with aggregates of complex I and mtDNA is lost. triggered apoptosis (22), and only TID1-S clusters acetylcholine receptors, leading to efficient synaptic transmission in neuromuscular junctions (26). Our data provide evidence that in mitochondria, the TID1-S and TID1-L isoforms are also functionally distinct.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…When ATP synthesis is inhibited, TID1 is recruited to a detergent-resistant fraction together with aggregates of complex I and mtDNA is lost. triggered apoptosis (22), and only TID1-S clusters acetylcholine receptors, leading to efficient synaptic transmission in neuromuscular junctions (26). Our data provide evidence that in mitochondria, the TID1-S and TID1-L isoforms are also functionally distinct.…”
Section: Discussionmentioning
confidence: 66%
“…S13 in the supplemental material). Interestingly, a previous report indicated that the Nterminal half (amino acids 1 to 222) of the TID1 protein is sufficient to induce neuronal acetylcholine receptor cluster clustering, suggesting that the C terminus is dispensable for its activity (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, Musk activity is regulated by Dok7 and Lrp4. Musk also interacts with tumorous imaginal discs (Tid1; also known as Dnaja3), which is necessary for Dok7 binding to Musk in response to agrin (Linnoila et al, 2008). Upon activation, Musk becomes rapidly internalized, which is required for AChR clustering (Zhu et al, 2008).…”
Section: Agrin/lrp4/musk Signalingmentioning
confidence: 99%
“…Analysis of the subcellular localization of Tid1 indicates that this DnaJ protein resides predominantly in the mitochondria (26). However, studies have also shown that Tid1 interacts with vast amounts of cytoplasmic and plasma membrane-bound cellular and viral proteins (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%